Advancement in agriculture approaches with agrivoltaics natural cooling in large scale solar PV farms - Othman, Noor Fadzlinda; Ya’acob, Mohammad Effendy; Lu, Li; Jamaluddin, Ahmad Hakiim; Mat Su, Ahmad Suhaizi; Hizam, Hashim; Shamsudin, Rosnah; Jaafar, Juju Nakasha (Multidisciplinary Digital Publishing Institute, 2023)
The increasing concerns about the impact of large-scale solar photovoltaic farms on the environment and the energy crisis have raised many questions. This issue is mainly addressed by the integration of agriculture advancement in solar photovoltaic systems infrastructure facilities, commonly known as agrivoltaic. Through the use of these systems, the production of crops can be increased, and the efficiency of PV panels can be improved. Accordingly, adopting such synergistic paths forward can contribute toward building resilient energy-generation and food-production systems. The utilization of cooling techniques can provide a potential solution for the excessive heating of PV cells and lower cell temperatures. Effective cooling applied to PV cells significantly improves their electrical efficiency, as well as increasing their lifespan because of decreasing thermal stresses. This paper shares an overview of both active and passive cooling approaches in solar PV applications with an emphasis on newly developed agrivoltaic natural cooling systems. Actual data analysis at the 2 MWp Puchong agrivoltaic farm shows a significant value of 3 increase of the DC generation (on average) which is most beneficial to solar farm operators.